2016
DOI: 10.1074/jbc.m116.744615
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 Glycoprotein Interacting with Dendritic Cell-specific Intercellular Adhesion Molecule 3-grabbing Non-integrin (DC-SIGN) Down-Regulates Tight Junction Proteins to Disrupt the Blood Retinal Barrier and Increase Its Permeability

Abstract: Approximately 70% of HIV-1 infected patients acquire ocular opportunistic infections and manifest eye disorders during the course of their illness. The mechanisms by which pathogens invade the ocular site, however, are unclear. Under normal circumstances, vascular endothelium and retinal pigment epithelium (RPE), which possess a well developed tight junction complex, form the bloodretinal barrier (BRB) to prevent pathogen invasion. We hypothesize that disruption of the BRB allows pathogen entry into ocular sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Nonetheless, their expression of CCR5, a critical coreceptor for HIV, suggests potential gp120 interaction leading to cellular dysfunction [36]. In our study, employing Maraviroc, a CCR5-specific antagonist [37], effectively mitigated gp120-induced AEG-1 upregulation, corroborating our preliminary findings [36]. Shi et al [38] observed elevated expressions of both CCR5 and AEG-1 in cardiac myxoma, potentially correlating with tumor size and disease progression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, their expression of CCR5, a critical coreceptor for HIV, suggests potential gp120 interaction leading to cellular dysfunction [36]. In our study, employing Maraviroc, a CCR5-specific antagonist [37], effectively mitigated gp120-induced AEG-1 upregulation, corroborating our preliminary findings [36]. Shi et al [38] observed elevated expressions of both CCR5 and AEG-1 in cardiac myxoma, potentially correlating with tumor size and disease progression.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, their expression of CCR5, a critical coreceptor for HIV, suggests potential gp120 interaction leading to cellular dysfunction [36]. In our study, employing Maraviroc, a CCR5-specific antagonist [37], effectively mitigated gp120-induced AEG-1 upregulation, corroborating our preliminary findings [36].…”
Section: Discussionsupporting
confidence: 86%
“…HIV has been found in retina, vitreous humor, iris, cornea, conjunctiva and tears (7)(8)(9). Breakdown of BRB was suggested as determinants of the positive intraocular HIV (10,11), and being on HAART had a signi cant impact on aqueous humor HIV RNA levels (12). In our study, the HIV VL in the eye showed a negative association with ART duration, indicating that su cient antiviral therapy would effectively reduce the HIV VL in the eye.…”
Section: Discussionmentioning
confidence: 46%
“…GM6001 was then added in the slice culture medium at a final concentration of 50 nM as a pretreatment, 1 h before the SCL. Fresh GM6001 was added every time the medium was replaced [75].…”
Section: Pharmaceutical Treatment For Mmps Modulationmentioning
confidence: 99%